Temporal Junctures in the Mind. Issue 1 (January 2020) - Redshaw, Jonathan; Suddendorf, Thomas
Abstract : Humans can imagine what happened in the past and what will happen in the future, but also what did not happen and what might happen. We reflect on envisioned events from alternative timelines, while knowing that we only ever live on one timeline. Considering alternative timelines rests on representations of temporal junctures, or points in time at which possible versions of reality diverge. These representations become increasingly sophisticated over childhood, first enabling preparation for mutually exclusive future possibilities and later the experience of counterfactual emotions like regret. By contrast, it remains unclear whether non-human animals represent temporal junctures at all. The emergence of these representations may have been a prime mover in human evolution. Highlights: Many recent studies have examined the development, evolution, dysfunctions, and neurocognitive mechanisms of the capacity to consider events from alternative timelines. Children begin to consistently prepare for alternative versions of immediate future events around 4 years of age, but do not accurately consider alternative versions of past events and present situations until around 6 years of age. There is no compelling evidence that non-human animals consider and compare events from alternative timelines, although interpretations of some results remain contentious. Representing alternative versions of the future enables humans to form contingency plans and otherwise compensate for their inability to perfectly predict future outcomes. Representing alternative versions of the past enables humans to learn associations not only between actual behaviours and outcomes, but also counterfactual behaviours and outcomes.